(3cJGH aj fbd CehGd GdeSGLO HYVgG Edi HYV hLhGH Pdcs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3QCjfG hQCi BHGFfG GdYed Ydi GdESJUdGM GdeQSd eeG cGf LGQjkG Ydi CUhd GdTQjYI s
(3BNQgG (B:s
(3hdG NQGH CYXe ef NdhgG Yf GdUdhGJ hGdYHGOGJ hOQS cJGH Gddg hJdGhJg hdQHeG cGf GdYei NjQ ef HUjQI Mhdi Je Pdc s
(3HgG fXGe GdJYbjHIs
(3QSGdI cJHgG GdeDda ddebQi Yaja GdOjf eSYhO Hf eMeO GdMhjJs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
Keywords: (3Gdabg GdESdGejs